Periodontite apical e diabetes mellitus – influência de uma condição sobre a outra: revisão de literatura - Soares, Carina Aparecida de Chaves; Poletto, Marina Caldas (My University, 2021)
Diabetes Mellitus is a systemic disease of metabolic uncontrol where there is a failure of insulin secretion by the pancreas or failure of insulin action in the tissues. Apical periodontitis is a periapical inflammatory and immune response to the presence of bacterial infection in the root canal. The aim of this study was to review the literature regarding the possible influence of diabetes mellitus on apical periodontitis and vice versa. The selected articles came from the PUBMED and LILACS databases, using the keywords: Diabetes mellitus; periradicular lesions; Diabetes; Apical Periodontitis. Based on a critical analysis of the scientific articles studied, a possible bidirectional relationship between both conditions was found, since the presence of diabetes mellitus alters the severity of apical periodontitis and apical periodontitis may cause insulin resistance, causing increased blood glucose levels. However, further studies are needed to confirm this association. Thus, the management of the patient with diabetes and associated apical periodontitis should be integral, so that the treatment of the conditions is effective. [resumo fornecido pelos autores]
Diabetes Mellitus é uma doença sistêmica de descontrole metabólico onde há uma falha na secreção de insulina pelo pâncreas ou falha na ação da insulina nos tecidos. A periodontite apical consiste em uma resposta inflamatória e imunológica periapical à presença de contaminação bacteriana no canal radicular. O objetivo do presente estudo foi revisar a literatura com relação à possível influência do diabetes mellitus sobre a periodontite apical e vice-versa. Os artigos selecionados foram oriundos das bases de dados PUBMED e LILACS, valendo-se das palavras chaves: Diabetes mellitus; periradicular lesions; Diabetes; Apical Periodontitis. Valendo-se da análise crítica dos artigos científicos estudados, verificou-se uma possível relação bidirecional entre ambas as condições, visto que a presença do diabetes mellitus altera a gravidade da periodontite apical e a periodontite apical pode ocasionar uma resistência à insulina causando aumento da glicemia. No entanto, mais estudos são necessários para confirmar tal associação. Desta forma, o manejo do paciente com diabetes e periodontite apical associadas deve ser integral, para que o tratamento das condições seja efetivo. [resumo fornecido pelos autores]
Keywords: Odontologia; Periodontite; Diabetes; Doenças periapicais - Diagnóstico